Pengaruh Kualitas Pelayanan dan Harga Terhadap Minat Berkunjung Kembali Wisatawan - Zakiatul Fitria; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aim stoanalyze service quality and price on the interest of returning tourists. The population of this research is visit or swho are visiting and visitors who have visited the Srikandi Polesincere ayu swimming pool in the sub-distric to foverlappingwith a total sample of 65 respondents. This research his a type of quantitative research that uses primary data and uses a questionnaire data analysis method. The questionnaire was distributed to respondents who had certain criteria to provide answers regarding the statements given by the researcher. The criteria for the sample of this research are visitors who are a tleast 5 year sold and over and visitors who have visitedor are currently visiting the Seikandi PoleTulusayu Swimming Pool, Tumpang District. To measure respondents' answers to the questionnaire using a Likert scale. This study uses multiple linear regression analysis method and the results study indicate that the quality o fservice has a positive but not significant effect and the price has a positive and significanteffect on the interest of returning to uriststo visitors to the Srikandi Pole Tulusayu Swimming Pool, Tumpang District. Keywords: qualityofservice, priceandinterest in returningtourists.